An investigation of the relationship between counterfeiting and culture: evidence from the European Union - Ribeiro, J. Cadima (2006)
International counterfeiting affects adversely producers, consumers and domestic economies. Some attempts have been made in the last years by international organisations (European Union, World Trade Organisation) to deal with this complex problem. Though some success has been achieved, the number of seizures of counterfeited goods detected in the external borders of EU has increased. This study examines the impact of Hofstede’s cultural variables (power distance, individualism, masculinity, uncertainty avoidance) on the level of counterfeiting in European countries.